Effects of earthworms on soil organic matter and nutrient dynamics at a landscape scale over decades - Lavelle, Patrick; Charpentier, Fabienne; Villenave, Cécile; Rossi, Jean Pierre; Derouard, Laurent; Pashanasi Amasifuen, Beto; Andre, Jean; Ponge, Jean François; Bernier, Nicolas (CRC Press, 2023)
After several decades of unquestioned success, agriculture is now facing important global problems. Huge increases in productivity in developed countries have been accompanied by a severe depletion of “soil quality” in terms of resistance to erosion, organic contents, concentrations of heavy metals, and pesticide residues. Agricultural intensification in developing countries has been less successful because of various socioeconomic limitations. Nevertheless, traditional agricultural practices do not conserve the quality of soils; stocks of organic matter are rapidly becoming depleted, and erosion removes fine particles from the soil surface horizons. In a context of increasing human population pressures, particularly in developing countries, this degradation of soils results in many social and environmental problems (Eswaran 1994; FAO 2000). Features common to all kinds of soil degradation are a significant decrease in organic reserves, degradation of the soil structure, and severe depletion of soil invertebrate communities, especially earthworms (Decaëns et al. 1994; Lavelle et al. 1994).